Study of Rheological Property and Flow Behavior for Nanoparticles Enhanced VES System in Porous Media - Liu, Zhaoxia; Wang, Qiang; Gao, Ming; Luo, Wenli; Cai, Hongyan (Frontiers in Energy Research, 2021)
In this paper, a composite sample (VES and SiO2 nanoparticle) was used to overcome the deficiencies of polymer. The rheological character of the VES/nanoparticles hybrid and flow behavior in porous media were examined. It was found that SiO2 nanoparticles exhibited viscosifying action and improved the oil tolerance. In addition, the VES solution without nanoparticles showed a lower capacity to recover oil, which might be attributed to the fact that wormlike micelles would be destroyed in crude oil. On the contrary, an enhanced oil recovery of 9.68% was achieved in the composited experiment for the VES sample with nanoparticles which is relatively stable with oil.